LEACHING KALIUM DARI ABU KULIT COKLAT (Theobroma cacao L.) MENGGUNAKAN PELARUT AIR - Lilis Sukeksi; Rizka Dwi Hidayati; Aulia Bismar Paduana (Jurnal Teknik Kimia USU, 2017)
Recently much attention has been dedicated to generate of useful chemicals from biomass, such as potassium alkali from cacao husk. This potassium can be used as sources of alkali for soap manufacturing. The cacao husks were treated by leaching using water as a solvent to produce alkali potash. First step, the cacao husks and then were dried at 105 ºC for 24 hours. The dried of cacao husk was crashed using ball mill and resulting husk powder were burned in a furnace at 600 ºC for 6 hours and resulting the husk ash powder. The husk ash powder mass variables used in this leaching process were 5 g, 7.5 g and 10 g and the leaching time variables were 30 minutes, 60 minutes and 90 minutes. Meanwhile the leaching temperature variables were 45 ºC, 55 ºC and 65 ºC. The best temperature condition in this process was 65 ºC and leaching time 60 minutes, with the result of potash concentration was 1,01 N and the amount of potash as a potassium hydroxide is 39,91% was analyzed using Atomic Absorption Spectroscop (AAS).